An assessment of the effectiveness of the existing signages in conveying information in a selected unit in the University of the Philippines Diliman - Martinez, Raymond L.
ABSTRACT The study sought to determine the effectiveness of the existing signages in conveying information in the public areas of a selected unit in University of the Philippines Diliman. Using a quasi-experimental research design, a wayfinding test among ten participants who have been purposively selected was conducted to meet the objectives of the study. This was supported by photo documentation, interview and survey. Secondary data were also collected as references. After the wayfinding test was conducted, a follow-up interview and survey among the ten wayfinding test participants were made. The interview results were coded and emerging themes and patterns were identified. A five-point Likert scale was used in the survey to obtain the participants? satisfaction rating for effectiveness of the messages contained in the signages and the elements of the signages. The triadic relationship of signified, signifier and interpretant as referred in Peircian semiotics was used as reference to further analyze the effectiveness of the signage. Results and findings showed that the existing signages in the selected unit in UPD have low effectiveness in conveying information. It was signified by the difficulty of the participants in finding their destinations using these signages. The inadequacy of information, inconsistency and inaccuracy of signages and deficient characteristics of the elements of these signages were some factors identified as causes of difficulty in wayfinding. The study recommends a more in-depth study on how users actually use the available signages and up to what extent signages are useful.